Tetanus Complicated by Dysautonomia: A Case Report and Review of Management - Nishant Sharma; Si Li; Metlapalli Venkata Sravanthi; Dan Kazmierski; Yichen Wang; Amit Sharma; Pragya Dhaubhadel (Case Reports in Critical Care)
Tetanus is a life-threatening infectious neurological disorder that is now a rare disease due to the institution of wide-spread vaccination strategies. We present an uncommon case of generalized severe tetanus with consequent respiratory failure requiring mechanical ventilation, which was associated with dysautonomia. A 20-year-old unvaccinated female presented with neck stiffness and diffuse muscle spasms following a laceration sustained 3 weeks prior. She was admitted to the intensive care unit for mechanical ventilation and was treated with immunoglobulin, tetanus toxoid, metronidazole, and high doses of sedatives. She also developed dysautonomia, with alternating bradycardia and tachycardia, as well as fluctuating blood pressure. She was successfully extubated and discharged. We also review the epidemiology, pathophysiology, and management of tetanus and discuss dysautonomia in the setting of tetanus.